Implications of Using Host Response-Based Molecular Diagnostics on the Management of Bacterial and Viral Infections: A Review - Atallah, Johnny; Mansour, Michael K. (Frontiers in Medicine, 2022)
Host-based diagnostics are a rapidly evolving field that may serve as an alternative to traditional pathogen-based diagnostics for infectious diseases. Understanding the exact mechanisms underlying a host-immune response and deriving specific host-response signatures, biomarkers and gene transcripts will potentially achieve improved diagnostic outcomes that will ultimately translate to better patient outcome. Several studies have focused on novel techniques and assays focused on immunodiagnostics. In this review article, we will highlight recent publications on the current use of host-based diagnostics alone or in combination with traditional microbiological assays and their potential future implications on diagnosis, prognostic accuracy for the patient with infectious complications. Finally, we will also address the cost-effectiveness implications from a healthcare and public health perspective.